One on one Caloocan blues ; Super 8 [videorecording] - Lazaro, Cheche (The Probe Team, 1990)
Features the controversy between PBA and the PABL regarding the composition of a bastketball team to represent the country in the Beijing Asean Games: the election controversy between OIC Mayor Dr. Martinez and declared winners Macario Asistio of Caloocan: and the TPT featuring their Super 8 Productions with the young aspiring directors.